Comparability of three intraocular pressure measurement: iCare pro rebound, non-contact and Goldmann applanation tonometry in different IOP group - Chen, Min; Zhang, Lina; Xu, Jia; Chen, Xinyi; Gu, Yuxiang; Ren, Yuping; Wang, Kaijun (BMC ophthalmology, 2019)
Background Measurement of intraocular pressure (IOP) is essential for glaucoma patients. Many factors such as central corneal thickness (CCT) can affect the accuracy of IOP measurement. The purpose of this study was to evaluate the agreement of IOP measured by non-contact tonometer (NCT), iCare pro rebound tonometer (iCare), and Goldmann applanation tonometer (GAT) in different IOP group. Methods This was a Hospital-based cross-sectional study. Two hundred subjects were enrolled in this study. All subjects underwent IOP measurement using an NCT–iCare–GAT sequence. Bland-Altman, Pearson correlation and intraclass correlation analysis were performed using SPSS 17.0 software. The influence of CCT on each IOP measurement methods was evaluated by linear regression analysis. Results The mean difference (Δ) of NCT–GAT did not differ from (Δ) iCare–GAT in IOP < 10 and 10–21 mmHg group. However, (Δ) NCT–GAT was significantly higher than (Δ) iCare–GAT in IOP 22–30 and > 30 mmHg group ( P < 0.05). Bland–Altman analysis showed significant agreement between the three devices ( P < 0.01). IOP measurements of the three methods were significantly correlated with CCT ( P < 0.01). Conclusions ICare pro shows a higher agreement with GAT over a wide range of IOP compared with NCT. The consistency between the three tonometers was similar in a low and normal IOP range. However, NCT shows a greater overestimate of IOP in moderate and higher IOP group. The variability of IOP measurement affected by CCT is NCT > iCare pro > GAT.